Археологические исследования ХНПУ на территории Харьковской обл. в 2008 г. - Колода, В.В.; Квитковский, В.И. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the main results of the work of Mediaeval expedition in Kharkiv Oblast. At the Pyatnytske settlement (Saltiv archaeological culture, the middle of the 8th — the middle of the 10th c. AD) the research was ongoing at the Trench 3 at the northern part of the site, where the remains of a dwelling with the kiln made of stones, two husbandry structures and several husbandry pits were studied. At the Trench 9, besides the mediaeval cultural layer the Bronze Age deposits of Zrubna culture of the 14th —12th c. BC were found. At the Mokhnach hill-fort three Early Mediaeval dwellings, two granaries, a cellar, a seasonal kitchen, and several husbandry pits were additionally researched. A new settlement with the materials of Saltiv culture is found at a distance of two kilometers to the north from the hill-fort. Foundation pits of the ancient dwellings are well recognizable on its surface.